Global approaches to Indigenous health through interprofessional education: a scoping review. - Mathur, Salina; Aydin, Cara; Cardinal, Samaria Nancy; Sangrar, Ruheena; Langlois, Sylvia (Journal of Interprofessional Care)
Indigenous communities worldwide experience inequalities in healthcare systems and face profound challenges in accessing equitable care. To bridge these gaps and deliver culturally safe healthcare, healthcare practitioners require appropriate education. Interprofessional education learning activities can facilitate understanding of beneficial and collaborative approaches to Indigenous health. This study explored the depth, breadth, and nature of existing literature on educational strategies used while teaching Indigenous health approaches within interprofessional education. The scoping review was guided by the Joanna Briggs Institute's methodology and considered all forms of English-language evidence with any publication date; it included quantitative, qualitative, mixed-method studies, and gray literature. Six databases were searched along with hand searching and reference list scanning. Sources were screened, extracted using a data extraction form, and analyzed quantitatively and qualitatively. The information was summarized using a summary of results table and a narrative summary. Of 1486 sources, 45 were included following a full-text review. An array of educational strategies informed by various theories and cultural concepts were extracted. Although the content of each learning activity was often unique to the local Indigenous community, many of the foundational theories and concepts were similar across cultures. The findings highlight the importance of partnering meaningfully with Indigenous individuals and communities in educational activity creation and delivery to enhance the quality of learning and learner satisfaction. These findings can contribute to developing culturally safe interprofessional healthcare services for Indigenous communities and guide the development of Indigenous health-related interprofessional education learning activities.